Trace elements and diabetes: Assessment of levels in tears and serum. (January 2017) - Cancarini, A.; Fostinelli, J.; Napoli, L.; Gilberti, M.E.; Apostoli, P.; Semeraro, F.
Abstract: Tear film is critical for the well-being and homeostasis of the ocular surface. Although the composition of the tear film is well known, the composition of metallic elements have yet to be analysed. Despite trace elements metabolism has been reported to play a role in the pathogenesis of diabetes mellitus, a metabolic disease that affects several aspects of homeostasis, little is known in the literature regarding concentration and possible variation of metallic elements in tear film. We studied the concentrations of several essential and non-essential metallic elements in the tear fluid and serum of patients with type II diabetes mellitus and a group of non-diabetic controls. Serum and tear fluid were collected from 97 patients: 47 type II diabetic patients and 50 non-diabetic controls. Regarding tear film, there were statistically significant differences in Zinc, Chrome, Cobalt, Manganese, Barium, and Lead between groups; the values of all metallic elements were found to be statistically significant higher in patients with mellitus type II diabetes. Regarding serum values there was a statistically significant difference in Chrome, Cobalt, and Selenium values; the concentrations of Chrome and Cobalt were higher in the control group, while Selenium concentration was higher in diabetic patients. In patients with type II diabetes, metal elements with higher concentrations in tears compared to serum were: Lead, Barium, Manganese, Cobalt, and Chrome. In the control group, the metal elements with the highest concentration in tear film compared to serum were Chrome, Manganese, Barium, and Lead. In this study, we attempted to evaluate the possible effect of a disease, such as diabetes, on the metabolism of metallic elements. Although our evidence was very interesting, it is probably limited in its accuracy due to the fact that individuals in the control group harboured ocular pathologies. This work lays the foundation for future studies. Highlights: Trace elements analysis in tears could be reliable biomarker. Zn, Cr, Co, Mn, Ba, and Pb in tears resulted higher in diabetic patients. Analysis of trace elements in serum showed not same differences. Alteration of same trace metals may play role in the development of diabetes mellitus.